The Nearby Evolved Stars Survey II: Constructing a volume-limited sample and first results from the James Clerk Maxwell Telescope. Issue 1 (17th March 2022) - Scicluna, P; Kemper, F; McDonald, I; Srinivasan, S; Trejo, A; Wallström, S H J; Wouterloot, J G A; Cami, J; Greaves, J; He, Jinhua; Hoai, D T; Kim, Hyosun; et al.
ABSTRACT: The Nearby Evolved Stars Survey (NESS) is a volume-complete sample of ∼850 Galactic evolved stars within 3 kpc at (sub-)mm wavelengths, observed in the CO J = (2–1) and (3–2) rotational lines, and the sub-mm continuum, using the James Clark Maxwell Telescope and Atacama Pathfinder Experiment. NESS consists of five tiers, based on distances and dust-production rate (DPR). We define a new metric for estimating the distances to evolved stars and compare its results to Gaia EDR3. Replicating other studies, the most-evolved, highly enshrouded objects in the Galactic Plane dominate the dust returned by our sources, and we initially estimate a total DPR of 4.7 × 10 −5 M⊙ yr −1 from our sample. Our sub-mm fluxes are systematically higher and spectral indices are typically shallower than dust models typically predict. The 450/850 μ m spectral indices are consistent with the blackbody Rayleigh–Jeans regime, suggesting a large fraction of evolved stars have unexpectedly large envelopes of cold dust.